TRADITIONAL GAMES IN IMPROVING LEARNING OUTCOMES OF SQUAT STYLE LONG JUMP IN ELEMENTARY SCHOOL STUDENTS - Alwi Fahruzy Nasution; Fatin Nadifa Tarigan; Yulia Tiara Tanjung (Universitas Negeri Medan, 2022)
This study aims to improve the learning outcomes of the squat-style long jump through traditional games in grade VI A SD Agung Persada Bandar Khalipah. The problem in this study is how to improve the squat style long jump through traditional games for elementary school students. The research method used in this research was classroom action research. The population in this study were all students Class VI SD Agung Persada Bandar Khalipah, Deli Serdang Regency with 37 students. From the data analysis that has been done, it can be concluded that using traditional games can have an influence and improve learning outcomes in the squat style long jump. Where in the first learning outcomes test, the research results obtained that the percentage of the average value after conversion was 66.18 and the student's classical learning completeness level was 56.76%. Therefore, traditional games can be used as materials for ways to convey learning to students.